Artaud’s Hyeroglyphic Sign and Böhme’s Aesthetics of Atmosphere: The Semiotic Legacy of the Avant-Garde’s Recognition of the Materiality of Sound - Ovadija, Mladen (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2015)
Materiality of the sign/sound in theatre appears when various sensory materials remain on the side of the signifier, not trying to reach the signified but energetically pulsating from the stage instead. The semiotics of sound would benefit from exploring the process where the theatrical sign or sound is caught naked in its flight between deliverance and reception, not yet clothed in its signifying dress. Such a semiotics follows oral/aural signs becoming other signs in the area where the senses signify. I suggest that voice and stage sound/noise figure as catalysts of an intermedial flux between sensual, visual, kinetic, and architectural elements of performance, marking a legacy of the avant-garde recognition of the materiality of sound. I demonstrate this using Artaud’s concept of a hieroglyphic idiom as the “expression in space [in which] objects themselves begin to speak through the collusion of objects, silences, shouts and rhythms,” and through Boehme's aesthetics of atmospheres as the art of the set that creates a poetics/technè of postdramatic theatre focused on orality/aurality.